Embedded institutions and the persistence of large farms in Russia; Die Bedeutung eingebetteter Institutionen für den Fortbestand landwirtschaftlicher Großbetriebe in Russland - Ulrich Koester; Martin Petrick (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
Differences in farm structures between Russia and western market economies can hardly be made consistent with the neoclassical textbook idea of a technologically determined farm size operating in a perfect market environment. The main aim of the paper is to identify embedded institutions that provide an explanation for the persistent differences. It is shown that these institutions vary widely across countries. We argue that the historical contingency of a patrimonial society that is both hierarchical and egalitarian also has an important bearing on the current persistence of large farming structures in Russia. The cultural beliefs based on this contingency explain the relative absence of entrepreneurial attitude in the rural society, the lack of trust in formal transactions with strangers, and the unwillingness to deviate from collective behaviour. Managers of former collective farms together with regional government authorities had strong incentives to secure their status-quo rents by inhibiting individualisation in agriculture. In addition, based on their ideological background in communism and their lifelong experience, many of them simply could not imagine how food security and social safety in the countryside should be provided without large farms. It is argued that the evolution of super-large farms could only arise because cooperative and corporate farms survived up to bankruptcy and because embedded institutions impeded the foundation of family farms. Mental models of policy makers did contribute to the amalgamation of corporations and cooperatives into super-large farms. The paper ends with an evaluation from the economic point of view of the existence of super-large farms and with a projection of what may happen in the future. – – Die Unterschiede in den Betriebsstrukturen zwischen Russland und den westlichen Marktwirtschaften lassen sich kaum mit dem neoklassischen Lehrbuchmodell einer technologisch determinierten Betriebsgröße in einem vollkommenen Markt in Einklang bringen. Das Hauptziel des Artikels besteht deshalb darin, die eingebetteten Institutionen zu identifizieren, die für die anhaltenden Unterschiede eine Erklärung liefern können. Es wird gezeigt, dass diese Institutionen von Land zu Land stark variieren. Wir vertreten den Standpunkt, dass die historische Bedingtheit der russischen Gesellschaft, die sowohl hierarchisch als auch egalitär geprägt ist, einen bedeutenden Einfluss auf das derzeitige Weiterbestehen der großbetrieblichen Strukturen in Russland hat. Die so geprägten kulturellen Vorstellungen und Überzeugungen der Handelnden erklären den relativen Mangel von unternehmerischem Verhalten in der ländlichen Gesellschaft, das fehlende Vertrauen in formale Transaktionen mit Fremden und den Unwillen, vom Kollektivverhalten abzuweichen. Die Leiter der ehemaligen Kollektivbetriebe und regionale Verwaltungen hatten starke Anreize, die Status-quo Renten ihrer Einnahmen zu sichern, indem sie eine Individualisierung der Großbetriebe verhinderten. Hinzu kommt, dass sich viele von ihnen aufgrund ihres ideologischen Hintergrunds im Kommunismus und ihrer lebenslangen Erfahrung einfach nicht vorstellen konnten, wie Nahrungsmittelsicherheit und soziale Absicherung auf dem Lande ohne Großbetriebe funktionieren sollten. Es wird vermutet, dass sich die neuerdings entstandenen, riesigen Agroholdings nur entwickeln konnten, weil die bisherigen Großbetriebe nicht liquidiert wurden und eingebettete Institutionen die Gründung von Familienbetrieben verhinderten. Die mentalen Modelle der Politiker trugen daher zum Verschmelzen der Großbetriebe zu Agroholdings bei. Der Artikel schließt mit einer Bewertung der Agroholdings aus ökonomischer Sicht und einem Ausblick in die Zukunft.
urn:nbn:de:gbv:3:2-10847
Keywords: P32; P52; Q12; Q15; 330; Embedded institutions; agricultural transition; farm restructuring; agroholdings; Russia; Eingebettete Institutionen; Transformation im Agrarsektor; Umstrukturierung; Agroholdings; Russland.